2009
DOI: 10.3354/meps07922
|View full text |Cite
|
Sign up to set email alerts
|

Egg trait variation in anchoveta Engraulis ringens: a maternal response to changing environmental conditions in contrasting spawning habitats

Abstract: The Engraulis ringens distribution (4 to 42°S) covers a wide variety of environmental conditions. We assessed the coping mechanisms used by this anchoveta in different spawning habitats, reporting differences in egg traits between populations off northern (Iquique, 20°S) and southern Chile (Talcahuano, 36°S) and throughout the spawning season. Eggs were smaller off Iquique, declined in size during the reproductive season (both populations), and inter-population differences persisted throughout the spawning sea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
33
0
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(35 citation statements)
references
References 30 publications
(39 reference statements)
0
33
0
2
Order By: Relevance
“…Our data on surface temperature at the coastal oceanographic stations as well as over the entire region confirm the difference in the thermal regime between these years for the anchoveta spawning zone. The hydrographic information for 2007 and wind data analyses carried out during the same months indicated that south winds occurred inducing upwelling at the coast in winter (Castro et al 2008), although downwelling usually occurs in the coastal zone during this season (Castro et al 2000). The different oceanographic conditions found in the 2 studied years also extended to the microand mesozooplankton composition.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…Our data on surface temperature at the coastal oceanographic stations as well as over the entire region confirm the difference in the thermal regime between these years for the anchoveta spawning zone. The hydrographic information for 2007 and wind data analyses carried out during the same months indicated that south winds occurred inducing upwelling at the coast in winter (Castro et al 2008), although downwelling usually occurs in the coastal zone during this season (Castro et al 2000). The different oceanographic conditions found in the 2 studied years also extended to the microand mesozooplankton composition.…”
Section: Discussionmentioning
confidence: 81%
“…In mid-winter 2005, mostly omnivorous and carnivorous small-sized copepods (Oncaeidae and Oithonidae) predominated, unlike winter 2007, when larger herbivorous-omnivorous calanoid copepods (mostly copepodites and adult Calanidae), typical of upwelling conditions, were predominant. In terms of zooplankton biomass, winter 2007 revealed the highest biomass values during the 7 yr time-series (Castro et al 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the higher biomass (mainly calanoids) in these stratified waters would contribute to the carbon transfer to the upper trophic levels and anchovy adults would be benefited. During winter, Castro et al (2009Castro et al ( , 2010 reported that variations in the biochemical composition of Engraulis ringens eggs in the upwelling system off the Chile coast were beneficial for young larvae. These authors found a negative relationship between egg size and food availability for larvae: smaller-sized copepods (presumably more prone to being captured by the youngest larvae) were most abundant when eggs were smaller because larvae would not need much lipid reserves to survive due to the abundance of small food sources in the sea.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings illustrate a trade-off mechanism between ovary weight (number of produced oocytes) and maternal 18:1 (n-9) supply to individual oocytes. Accordingly, Peruvian anchoveta Engraulis ringens (Jenyns, 1842) produced smaller amounts of eggs, albeit of larger sizes and lipid contents, to enhance egg and larvae survival under conditions with low water temperatures and low prey abundances (Castro et al 2009). EFA ratios remain more or less constant across the first 3 trophic levels of the food chain (St. John & Lund 1996).…”
Section: Discussionmentioning
confidence: 99%